Is preoperative hypoproteinemia associated with colorectal cancer stage and postoperative complications? - Amina Sofić; Ismar Rašić; Emsad Halilović; Alma Mujić; Denis Muslić (Medicinski glasnik, 2021)
Aim: To investigate the relationship between preoperative level of serum albumin in patients with colorectal cancer (CRC), stage of CRC and postoperative complications. Methods: This cross-sectional retrospective study was conducted at the Clinic for General and Abdominal Surgery of the University Clinical Centre Sarajevo (UCCS). A total of 107 patients surgically treated for CRC in the period between 2013 and 2018 were enrolled in this study and divided into two groups: with hypoalbuminemia (group A) and without hypoalbuminemia (group B). Results: The average level of albumin in group A was 29 (25-32) g/L versus 39 (37-41) g/L in group B (p<0.05). The average length of hospital stay in group A was 18 (13-25) days, and in group B 14.5 (12-21) days. Patients with hypoalbuminemia (group A) had wound dehiscence more often and more re-interventions compared to group B (p<0.05). Binary logistic regression found that serum protein, albumin and globulin levels were not statistically significant in the prediction of CRC stadium or postoperative complications (p>0.05). Conclusion: Study results show that preoperatively measured levels of serum albumin are not associated with the stage of colorectal cancer and cannot serve as predictors for postoperative complications.
Keywords: colorectal neoplasms; complications; postoperative period; serum